The underground movement in Austria : what the underground anti-nazi struggle is really like : a sober and informed account of revolutionary organisation under nazism - Czernetz, Karl (London: National Labour Press; Controversy Publishing Co., 1942)
"by Karl Czernetz Bibliotheek Camille HuysmansThemanummer van Left, april 1942 nr 67"